Animals without backbones / Ralph Buchsbaum - Buchsbaum, Ralph (1907)
Introduction, sorting out living things, life activities, simple and complex protozoans, variations on a one-celled theme, a side issue, sponges, two layers of cells, stinging-celled animals, comb jellies, three layers of cells, new parts from old, messmates and parasites, one-way traffic, proboscis worms, roundworms, lesser lights, soft-bodied animals, segmented worms, lobsters and other arthropods, crustaceans, arthropods on land, arachnids, airborne arthropods, insects, spiny-skinned, chordate beginnings.